When she was good : a novel - Robotham, Michael, 1960- (Scribner, 2020)
A sequel to "Good Girl, Bad Girl" finds criminal psychologist Cyrus Haven uncovering answers about Evie Cormac's dark past that force the latter to flee and question whether or not her secrets should remain hidden.